Contestation of Islamic Radio in the Development of Public Religion in North Sumatera: Case Study of Radio Broadcasts Arrisilah 95.7 Fm Deli Serdang - Pathurohman Pathurohman; Azhar; Hasrat Effendi Samosir; Mubarak Bamualim (WARAQAT : Jurnal Ilmu-Ilmu Keislaman, 2024)
All communities must be involved in the country's development process. Including radio media, it plays a role in the desired social change, plays an active role, contributes positively and is useful. This study aims to look at the role of Arrisilah FM Deli Serdang radio media in conveying religious development messages. The research method uses a qualitative approach with descriptive analysis carried out on the Arrisilah 95.7 FM Deli Serdang radio program. The results of the study state that Arrilahan FM Radio is a mass media that participates in developing the community of North Sumatra in the field of religion by presenting good programs so that it has superior programs in the listener's day. which has the best religious value in North Sumatra at the 2014 and 2015 KPID Award. However, on the other hand, there is a weakness, namely the reach of Arrilahan 95.7FM Deli Serdang radio. Not all areas of North Sumatra can listen to broadcasts easily, this is proven by the small number of direct interactions. However, Arrisilah FM radio tries to contribute to community development, especially in the field of religion.